The Effect of Smoking Behavior on the Incidence of Hypertension in the ≤45-Year Age Group at Efarina Hospital Berastagi - Ayu Juwita; Nur Rahmat Suhuda; Ella Novita (Sean Institute, 2026)
Background: Hypertension is an asymptomatic condition in which abnormally high pressure in the arteries causes an increased risk of stroke, aneurysm, heart failure, heart attack and others. One of the causes of hypertension is smoking, and smoking has become the consumption of many people including the teenagers or people in productive age. Aim: To determine the correlation between smoking behavior and hypertension of people in usia ≤ 45 years old ini Efarina Hospital. Method: This study employed correlational analytic design with cross-sectional approach. There were 183 respondents recruited as the sample through probability sampling with random sampling technique. The data were collected using observation sheets, sphygmomanometer tools and questionnaire. Further, the data used was bivariate data analysis with Spearman’s Rho test. Finding: The study found that based on statistical analysis test, the p-value (sig) was 0.000 (<0.05), which meant that there was a correlation between smoking behavior and hypertension of productive age people at Efarina Hospital. The significant correlation value = -.397. Conclusion: There is a correlation between smoking behavior and the incidence of hypertension with a significant correlation value of -.397 which means that the higher the smoking behavior, the better the incidence of hypertension.